Analysis of Aloe vera cytotoxicity and genotoxicity associated with endodontic medication and laser photobiomodulation - Carvalho, Nayane Chagas; Guedes, Simone Alves Garcez; Albuquerque-Júnior, Ricardo Luiz Cavalcanti; de Albuquerque, Diana Santana; de Souza Araújo, Adriano Antunes; Paranhos, Luiz Renato; Camargo, Samira Esteves Afonso [UNESP]; Ribeiro, Maria Amália Gonzaga (Elsevier, 2018)
This study aims to evaluate, in vitro, the effect of Aloe vera associated with endodontic medication, with or without laser photobiomodulation (FTL) irradiation in FP6 human pulp fibroblasts. The materials were divided into eight groups: CTR - control; CL - FTL alone; AA - Aloe vera with distilled water; AL - Aloe vera with distilled water and FTL; HA - calcium hydroxide P.A. with distilled water; HL - calcium hydroxide P.A. with distilled water and FTL; HAA - calcium hydroxide P.A. with Aloe vera and distilled water; HAL - calcium hydroxide P.A. with Aloe vera, distilled water, and FTL. The cytotoxicity was evaluated by MTT assay at 24, 48, and 72 h and the genotoxicity by micronucleus test assay. This study was performed in triplicate. Data obtained in both tests were statistically analyzed by ANOVA and Tukey's tests (p ≤ 0.05). Group AA presented high genotoxicity and low cytotoxicity. After 24, 48, and 72 h, the group HAA significantly reduced the cell viability. Interaction with FTL showed slightly increase cell viability after 24 and 48 h in groups CL and HL (p < 0.001), despite the high genotoxicity in group CL and low genotoxicity in group HL. Group AL showed higher cell survival rate at 72 h (p < 0.05) and high genotoxicity (p < 0.001). It was concluded that Aloe vera allowed higher cell viability in human pulp fibroblasts in the presence of calcium hydroxide or with FTL separately, but genotoxicity increased in these associations.
Keywords: Aloe vera; Cytotoxicity; Endodontic medication; Genotoxicity; Laser photobiomodulation